Mapping Evaluation Management Practices in International Research and Development Organizations - Toma, Irene; Jouini, Ibtissem; Maciel Pinto, D. (CGIAR Independent Advisory and Evaluation Service, 2025)
This study explores how evaluation management practices affect the use of evaluation findings and recommendations in decision-making, policies, and actions. It maps practices across independent evaluation entities and highlights perceptions of evaluation use in AR4D and multilateral organizations. Triangulation of data from multiple sources and methods underpinned the analysis.